Swift, brokered and broad-based information exchange: how network structure facilitates stakeholders monitoring EU policy implementation. (6th July 2018) - Schrama, Reini
Abstract: Monitoring the implementation process in domestic settings of multi-level policies like the EU gender directives is dependent on interactions among a diverse set of policy stakeholders. However, there is no clear understanding of which factors determine the structure of these monitoring networks and what benefits effective exchange. Drawing on insights from social network theory, literature on information politics in transnational networks and policy network analysis, this study analyses what drives information exchange among actors in the monitoring network of women's groups in the Netherlands. Using Exponential Random Graph Models, the analysis reveals distinctive structural features facilitating efficient information exchange and significant brokerage in the monitoring network. Moreover, the results demonstrate that interactions that serve the purpose of monitoring EU policy implementation occur among a diverse set of actors in a multi-level structure. These findings indicate that effective monitoring requires resourceful and broad-based information exchange to increase transparency in the implementation process.